2021
DOI: 10.4000/rfst.1268
|View full text |Cite
|
Sign up to set email alerts
|

Five Primary care teams facing the Covid Pandemic : analysis of territorial mobilizations

Abstract: La Revue francophone sur la santé et les territoires est mise à disposition selon les termes de la Licence Creative Commons Attribution -Pas d'Utilisation Commerciale -Partage dans les Mêmes Conditions 4.0 International.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This increased collaboration may also have been facilitated by sharing of resources (financial means, protocols, workforce), prior to the pandemic, that could be rapidly mobilized during the pandemic. The role of interprofessional practice, in France, during the pandemic has been documented in some qualitative studies [16,47]. Moreover, we have reported that interdisciplinary practice played an essential role for assuring care continuity for frail patients during the pandemic [48].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This increased collaboration may also have been facilitated by sharing of resources (financial means, protocols, workforce), prior to the pandemic, that could be rapidly mobilized during the pandemic. The role of interprofessional practice, in France, during the pandemic has been documented in some qualitative studies [16,47]. Moreover, we have reported that interdisciplinary practice played an essential role for assuring care continuity for frail patients during the pandemic [48].…”
Section: Discussionmentioning
confidence: 77%
“…In France, some centers were closed after only a few months, whereas others evolved to offer diagnostic tests and vaccinations. Overall, centers organized within pre-existing primary care structures seemed to be more efficient in adapting their resources to the pandemic and healthcare needs (e.g., pandemic waves and vaccination strategies) [16]. They also tended to exist for longer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation